Analisis Morfologi Permukaan Lapisan Klorofil dengan Atomic Force Microscopy: Lidya Nur De Vega, Suharyana, Budi Purnama - Lidya Nur De Vega, Lidya Nur De Vega; Suharyana, Suharyana; Budi Purnama, Budi Purnama (Jurnal Fisika dan Aplikasinya, 2025)
Surface morphological characteristic of chlorophyll layer have been analized. Chlorophyll layer deposited by spin coating methods on a glass coated ITO substrates. Results of morphological observation by AFM (Atomic Force Microscopy) explains that a thin layer with N = 5 has a flatter surface than with N = 3 due to inter molecular interaction process. The molecular size of the chlorophyll layers form a Gaussian distribution. From the profile curves, thickness of the layer were obtained as 287,9 and 372,6 nm for N =3 and 5 respectively.